Effects of inbreeding on behavioural plasticity of parent–offspring interactions in a burying beetle. (29th May 2020) - Ratz, Tom; Perodaskalaki, Anastasia; Moorad, Jacob; Smiseth, Per T.
Abstract: Inbreeding depression is defined as a fitness decline in progeny resulting from mating between related individuals, the severity of which may vary across environmental conditions. Such inbreeding‐by‐environment interactions might reflect that inbred individuals have a lower capacity for adjusting their phenotype to match different environmental conditions better, as shown in prior studies on developmental plasticity. Behavioural plasticity is more flexible than developmental plasticity because it is reversible and relatively quick, but little is known about its sensitivity to inbreeding. Here, we investigate effects of inbreeding on behavioural plasticity in the context of parent–offspring interactions in the burying beetle Nicrophorus vespilloides . Larvae increase begging with the level of hunger, and parents increase their level of care when brood sizes increase. Here, we find that inbreeding increased behavioural plasticity in larvae: inbred larvae reduced their time spent associating with a parent in response to the length of food deprivation more than outbred larvae. However, inbreeding had no effect on the behavioural plasticity of offspring begging or any parental behaviour. Overall, our results show that inbreeding can increase behavioural plasticity. We suggest that inbreeding‐by‐environment interactions might arise when inbreeding is associated with too little or too much plasticity in response to changing environmental conditions. Abstract : The magnitude of inbreeding depression often varies with environmental conditions, which could reflect that inbreeding alters phenotypic plasticity. We tested this hypothesis by comparing responses to environmental change of behavioural traits expressed in parent‐offspring social interactions. We found that inbreeding can increase behavioural plasticity, suggesting that inbreeding‐by‐environment interactions might arise when inbreeding is associated with too little or too much plasticity.